Perkembangan Kapasitas Fiskal dan Ruang Fiskal Kota Kupang, 2010-2019 - Frits O Fanggidae (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2020)
In the last 10 years (2010-2019), the fiscal capacity and fiscal space of the City Government of Kupang have increased every year. This increase has had a positive impact on increasing regional fiscal solvency and widening discretion for Regional Heads to finance their priority programs. In its dynamics, the amount of capacity and fiscal space is very sensitive to changes in PAD. Every increase in PAD of 1% can increase fiscal capacity by 2.69% and fiscal space by 2.11%. With the increase in PAD, it is very important to increase the capacity and regional fiscal space. The intended increase in PAD can be carried out systematically, measurably and continuously, through extensification and intensification of the regional revenue base.